El derecho de las víctimas en el derecho penal ecuatoriano. - Castillo Guzman, Carlos Eduardo (2013)
In the framework of a constitutional state guarantor of rights, which must be strengthened on the basis of respect, this study aims to visualize the fundamental rights of victims in criminal proceedings Ecuador, assuming that it is the main affected by the offense, legitimate interest in the process and yet the role that has corresponded traditionally minimal, although the supreme law from years ago in our legislation recognizes their rights, but the judicial system, has not found a way to apply and respect this has placed him in constant helplessness, hence the importance of addressing the issue.